Vibration properties of a rotating piezoelectric energy harvesting device that experiences gyroscopic effects. (3rd March 2018) - Lu, Haohui; Chai, Tan; Cooley, Christopher G.
Abstract: This study investigates the vibration of a rotating piezoelectric device that consists of a proof mass that is supported by elastic structures with piezoelectric layers. Vibration of the proof mass causes deformation in the piezoelectric structures and voltages to power the electrical loads. The coupled electromechanical equations of motion are derived using Newtonian mechanics and Kirchhoff's circuit laws. The free vibration behavior is investigated for devices with identical (tuned) and nonidentical (mistuned) piezoelectric support structures and electrical loads. These devices have complex-valued, speed-dependent eigenvalues and eigenvectors as a result of gyroscopic effects caused by their constant rotation. The characteristics of the complex-valued eigensolutions are related to physical behavior of the device's vibration. The free vibration behaviors differ significantly for tuned and mistuned devices. Due to gyroscopic effects, the proof mass in the tuned device vibrates in either forward or backward decaying circular orbits in single-mode free response. This is proven analytically for all tuned devices, regardless of the device's specific parameters or operating speed. For mistuned devices, the proof mass has decaying elliptical forward and backward orbits. The eigenvalues are shown to be sensitive to changes in the electrical load resistances. Closed-form solutions for the eigenvalues are derived for open and close circuits. At high rotation speeds these devices experience critical speeds and instability.